LGBT students’ short range narratives and gender performance in the EFL classroom - Rondón Cárdenas, Francisco (Colombian Applied Linguistics Journal, 2012)
By means of the analysis of six short range narratives, utilizing as a methodology (Feminist Post –Structuralist Discourse Analysis) FPDA, this paper unveils some significant moments which evidence the way LGBT EFL students draw on different discourses to adapt, negotiate, resist, emancipate, and reproduce heteronormativity. EFL students Methodological Framework Constantly shift positions and perform their gender assuming simultaneously powerful and powerless stances in the EFL classroom. The study categorizes the emancipatory discourse as a way to resist, the discourse of vulnerability as a way to reproduce and cope with marginalization, and the homophobic discourse as a way to position LGBT individuals as abnormal. Finally, the article will reflect on the moments LGBT student mitigate their oral skills and constrain their participation in class, due to the fact that they are frequently evaluating their comments to avoid accidental disclosure of their sexual identity.